Program Pemeliharaan Tenaga Kerja Front Office di Hotel Inc Bandung - Luthfi Aditya Nurhakim; Muhammad Arvel Kelvianto (Tamasya : Jurnal Pariwisata Indonesia, 2025)
In the increasingly competitive hospitality industry, the role of the front office has become very crucial because it is the first and last point of interaction between hotels and guests. The operational success of a hotel is largely determined by the performance of the workforce in the front office, which directly affects the first impression, guest satisfaction, and overall reputation of the hotel. This study discusses in depth the importance of the Front Office Workforce Maintenance Program at Hotel Room Inc Bandung as a human resource management strategy to improve service performance. The program covers various aspects, such as providing regular training, developing communication skills, understanding guest management, and improving employee well-being, motivation, and loyalty. The main goal of this program is to minimize turnover rates, improve workforce competence, and maintain optimal hotel service standards. Through this approach, hotels can create a conducive working atmosphere, consistent service, and a memorable stay experience for guests. The findings in this study indicate that investment in workforce maintenance directly has a positive impact on service quality and guest satisfaction, which is the key to success in the modern hospitality industry.